2020
DOI: 10.3390/met10020248
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Heat Treatment on the Oxidation Resistance of Cobalt-Based Superalloys

Abstract: Degradation of the mechanical integrity of cobalt-based superalloys can occur as the carbide network is progressively oxidised during high temperature service. In this study, a heat-treatment aimed at redistributing the carbides was tested on two similar commercial Co-based superalloys, one with high C content (Co-101) and one with low C content (Stellite-21), to determine its influence on oxidation resistance. It was found that the carbide phases in the lower C-containing alloy could be solutioned more readil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…It is well known that oxidation resistance is one of the most important aspects of nickel-based superalloys since poor oxidation resistance hinders their possible applications at high temperatures [12]. The oxidation behaviors of advanced nickel-based superalloys at temperatures higher than 700 • C have been studied extensively [19][20][21][22]. Brenneman et al [19] studied the oxidation behavior of GTD111 superalloy at 900 • C in air and concluded that the oxidation resistance was provided by the continuous dense Cr 2 O 3 oxide band, rather than the discontinuous Al 2 O 3 oxide layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that oxidation resistance is one of the most important aspects of nickel-based superalloys since poor oxidation resistance hinders their possible applications at high temperatures [12]. The oxidation behaviors of advanced nickel-based superalloys at temperatures higher than 700 • C have been studied extensively [19][20][21][22]. Brenneman et al [19] studied the oxidation behavior of GTD111 superalloy at 900 • C in air and concluded that the oxidation resistance was provided by the continuous dense Cr 2 O 3 oxide band, rather than the discontinuous Al 2 O 3 oxide layer.…”
Section: Introductionmentioning
confidence: 99%
“…Berthod et al [20] studied the oxidation behavior of six (Co + Ni)-based Cr-rich alloys with different Co/Ni ratios at 1250 • C and concluded that the higher the Ni content, the better the oxidation resistance of the alloys. Moffat et al [21] studied the oxidation behavior of a carbide network in low or high carbon Co-based superalloys at 1000 • C. They concluded that the carbide in low carbon alloys is more soluble than that in high carbon alloys, thus reducing the continuity of the carbide network and ultimately leading to an increase in the thickness of the oxide layer. Xiao et al [24] studied the cyclic oxidation behavior of Pt-modified γ' nanocrystalline coating at 1150 • C and confirmed that the nanocrystalline structure promoted the formation of α-Al 2 O 3 oxide coating with lower Pt and Al contents, which improved the anti-spalling performance.…”
Section: Introductionmentioning
confidence: 99%
“…Applications of these alloys include gas turbines, aircraft engines, and chemical reactors [4][5][6]. The Co-based superalloys are often alloyed with chromium to provide oxidation resistance [7,8]. The superalloys alloyed with Cr form a compact chromia scale (Cr 2 O 3 ) on their surface.…”
Section: Introductionmentioning
confidence: 99%